Instruments in the Redeemer's hands : people in need of change helping people in need of change - Tripp, Paul David, 1950- (Phillipsburg, New Jersey : P&R Publishing, 2002)
We might be relieved if God placed our sanctification only in the hands of trained professionals, but that is not his plan. Instead, through the ministry of every part of the body, the whole church will mature in Christ. Paul David Tripp helps us discover where change is needed in our own lives and the lives of others. Following the example of Jesus, Tripp reveals how to get to know people and how to lovingly speak truth to them. - Back cover.
The best of news : a reason to get up in the morning -- In the hands of the Redeemer -- Do we really need help? -- The heart is the target -- Understanding your heart struggle -- Following the Wonderful Counselor -- Building relationships by entering their world -- Building relationships by identifying with suffering -- Getting to know people -- Discovering where change is needed -- The goals of speaking the truth in love -- The process of speaking the truth in love -- Establishing agenda and clarifying responsibility -- Instilling identity with Christ and providing accountability -- Appendix 1: Opening blind eyes : another look at data gathering -- Appendix 2: What the counselor brings to the process of data gathering -- Appendix 3: Strategies for data gathering -- Appendix 4: Doctrines that drive homework -- Appendix 5: Homework and four phases of counseling.
Includes bibliographical references (pages 355-356) and index.
Description based on print version record.
Added to collection customer.56279.3
Keywords: Peer counseling in the church; Peer counseling in the church; Electronic books